Dehydroepiandrosterone and Its CYP7B1 Metabolite 7α-Hydroxydehydroepiandrosterone Regulates 11β-Hydroxysteroid Dehydrogenase 1 Directions in Rat Leydig Cells - Zhu, Qiqi; Dong, Yaoyao; Li, Xiaoheng; Ni, Chaobo; Huang, Tongliang; Sun, Jianliang; Ge, Ren-Shan (Frontiers in Endocrinology, 2020)
Background: The purpose of this study was to investigate cytochrome P450-7B1 (CYP7B1) in the human and rat testes to regulate 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) activity. We hypothesized that dehydroepiandrosterone (DHEA) and its product 7α-hydroxydehydroepiandrosterone (7αOHD) after catalysis of CYP7B1 played a critical role in driving the direction of 11β-HSD1, because 7αOHD is an alternative substrate for 11β-HSD1. Methods: We examined the influence of DHEA and 7αOHD on 11β-HSD1 activities in both intact Leydig cells and microsomes using radioactive substrates and identified the location of CYP7B1 in Leydig cells using immunohistochemical staining, Western blot, and qPCR. Results: We found that DHEA stimulated 11β-HSD1 oxidase activity in intact cells (EC50 = 0.97 ± 0.11 μM) and inhibited its reductase activity (IC50 = 1.04 ± 0.06 μM). In microsomes, DHEA was a competitive inhibitor of the reductase activity. The 11β-HSD1 oxidase activity in intact cells was inhibited by 7αOHD (IC50 = 1.18 ± 0.12 μM), and the reductase activity was enhanced (EC50 = 0.7 ± 0.04 μM). 7αOHD was a competitive inhibitor of 11β-HSD1 oxidase. CYP7B1 was present in rat Leydig cells, as shown by immunohistochemistry, Western blotting, and qPCR analysis. Conclusion: Our results are consistent with a conclusion that DHEA in the circulation driving 11β-HSD1 toward an oxidase in Leydig cells mainly through inhibiting the reductase of the enzyme, while 7αOHD (CYP7B1 catalytic product of DHEA) drives the enzyme toward the opposite direction.